Paradigma Baru Pendidikan dan Perkembangannya di Era Society 5.0 - Marantika, Juliaans; Tomasouw, Jolanda (Universitas Pattimura, 2024)
New Paradigm Learning or Merdeka Curriculum is learning that is oriented towards strengthening competencies and developing characters in accordance with the dimensions of the Pancasila Student Profile. This service aims to facilitate teachers in West Seram Regency to change their way of thinking about education that develops in this society 5.0 era so that the learning process that is built is more innovative and creative and students experience a better transfer of knowledge. The target of the service was 45 teachers from elementary to high school / MA and was carried out at MA Gemba. The activity took place with an interactive lecture model. To measure the achievement of this service activity, information about the satisfaction of the participants following the activity was collected through a questionnaire that was filled out. The results of the questionnaire showed that more than 85% of the participants strongly agree with this activity so that it has an impact on the learning process activities that are more innovative. The hope of the service activity is to conduct workshops to implement all activities.